Morphological analysis of pollen grains in Machaerium species from São Paulo, Brazil - Gusman, Vitória Húngaro Bocutti [UNESP]; Soares, Eduardo Lopes; de Souza, Cintia Neves [UNESP]; Cerdan, Isaura de Paula; Lopes, Ana Carolina Venancio; Gasparino, Eduardo Custódio [UNESP] (FapUNIFESP (SciELO), 2024)
Pollen morphology serves as a valuable tool for taxonomic characterization and evolutionary studies. In this study, we conducted a detailed morphological analysis of pollen grains from 16 species of Machaerium Pers. (Fabaceae) occurring in São Paulo, Brazil. Pollen samples were obtained from herbarium specimens and subjected to both qualitative and quantitative analyses using light microscopy and scanning electron microscopy. Our results confirm the stenopalynous character of Machaerium pollen, characterized by monads, isopolar pollen grains, 3-colporate with narrow colpi, and microreticulate exine. Quantitative measurements of colpus length and width, and endoaperture width, proved to be relevant for species differentiation. Additionally, qualitative characteristics such as pollen size, amb, shape, aperture position, presence of fastigium, and the thickness of the exine layer were identified as distinguishing factors among species. Despite variations observed, our analysis did not reveal distinct pollen features for taxonomic sections within the genus, indicating a high degree of pollen similarity among species. These findings contribute to our understanding of pollen morphology in Machaerium species and highlight the importance of pollen characteristics in taxonomic studies and evolutionary research.
Keywords: Cerrado; Fabaceae; Multivariate analysis; Palynology; Papilionoideae